1998
DOI: 10.1042/bj3320067
|View full text |Cite
|
Sign up to set email alerts
|

Structural and spectroscopic studies of azide complexes of horse heart myoglobin and the His-64→Thr variant

Abstract: The high-resolution X-ray crystallographic structures of horse heart azidometmyoglobin complexes of the wild-type protein and the His-64-->Thr variant have been determined to 2.0 and 1.8 A respectively. Azide binds to wild-type metmyoglobin in a bent configuration with an Fe-N-1-N-3 angle of 119 degrees and is oriented into the distal crevice in the direction of Ile-107. The proximity of the His-64 NE2 atom to the N-1 atom of the bound azide indicates stabilization of the ligand by the His-64 side chain throug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
1

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(40 citation statements)
references
References 43 publications
3
36
1
Order By: Relevance
“…Moreover, the positive charge on N(1) is increased by the negative charge of the iron-bound nitrogen atom, N(3), which is hydrogen-bonded to the amide group of Gly-143. Taking this molecular polarization into account, an asymmetric resonance structure is dominant for the azide bound to HO-heme, as proposed previously for the myoglobin complex with azide (28). Tyr-58, Arg-136, and Asp-140 are all conserved in mammalian HO-1 and HO-2 and in Corynebacterium diphtheriae HO, indicative of their importance in the hydrogen-bonding network.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Moreover, the positive charge on N(1) is increased by the negative charge of the iron-bound nitrogen atom, N(3), which is hydrogen-bonded to the amide group of Gly-143. Taking this molecular polarization into account, an asymmetric resonance structure is dominant for the azide bound to HO-heme, as proposed previously for the myoglobin complex with azide (28). Tyr-58, Arg-136, and Asp-140 are all conserved in mammalian HO-1 and HO-2 and in Corynebacterium diphtheriae HO, indicative of their importance in the hydrogen-bonding network.…”
Section: Discussionmentioning
confidence: 76%
“…On the addition of azide to HO-heme, low spin shift of the Soret band in the optical spectrum occurs (19,27), indicative that azide coordinates to the ferric heme iron. In the case of myoglobin, azide is bound parallel to the heme plane as dioxygen (28). The binding mode of azide provides a model of dioxygen (hydroperoxide) binding to HO-heme.…”
mentioning
confidence: 99%
“…Mb molecule was taken from its crystallographic data and assumed to be 10 nm 2 [44]. It was shown that a full monolayer coverage corresponds to 10 17 molecules/m 2 (or 1.66 x 10 -11 mol cm -2 ).…”
Section: Cyclic Voltammetry Of Myoglobinmentioning
confidence: 99%
“…These two classes of compounds were investigated because of their intense infrared transitions and ideal frequencies (see Table 3). The azide ion has already been used in infrared studies as a ligand bound to the heme iron of myoglobin (28). The successful incorporation of organic azides into proteins by the Tirrell lab (29) suggests that this vibration might be used as a general probe in proteins.…”
Section: Nitrilesmentioning
confidence: 99%